The market for virtue : the potential and limits of corporate social responsibility - Vogel, David, 1947- (Brookings Institution Press, 2005)
The principles and practices of corporate social responsibility (CSR) date back more than a century, but the current wave of interest in this topic is unprecedented. This heightened attention is global and is evidenced on every conceivable measure. It is reflected in the growth of social and ethical investment funds, the dramatic increase in voluntary codes of conduct for companies and industries, and the number of companies that issue reports on their social and environmental practices and policies. Similarly, the mobilization of nongovernmental organizations to challenge a wide range of corporate environmental and human rights practices, the frequency of consumer boycotts and protests, and the number of organizations and institutions established to monitor, measure, and report on corporate social and environmental performance all demonstrate deep grassroots interest. In this book, David Vogel provides the first comprehensive, in-depth review of the contemporary CSR movement in both the United States and Europe. He presents a careful and balanced appraisal of the movement's accomplishments and limitations, including a critical evaluation of the business case for CSR. While acknowledging the movement's achievements, most notably in improving some labor, human rights, and environmental conditions in developing countries, he also demonstrates that CSR's potential to bring about a significant change in corporate behavior is exaggerated. The Market for Virtue explores to what extent future improvements in corporate conduct can occur without more extensive or effective government regulation -- in the United States, Europe, the Far East, and in the developing countries. In other words, whatis the long-term potential of business self-regulation? Vogel concludes that the amount of improvement that can be expected is far more modest than much contemporary writing on corporate responsibility has claimed. There is a market for virtue, but it is limited by the substantial costs of more responsible business behavior.